Dinamika Interaksi Bahasa dalam Masyarakat Perkotaan Multikultural: Analisis Lingkungan Linguistik Sosial-Budaya - Christanto Syam; Sesilia Seli; Wamaungo Juma Abdu (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
This research undertakes a thorough exploration of the intricate dynamics characterizing socio-cultural linguistic interactions within multicultural urban communities, with a specific emphasis on language usage patterns. Employing a qualitative methodology, the study meticulously examines data gathered through participatory observation and interviews conducted with individuals representing diverse cultural and linguistic backgrounds. The findings illuminate the central role played by identity, power dynamics, and stereotypes in shaping the formation and utilization of language within the complex tapestry of multicultural societies. Individuals navigate their language choices based on perceived power dynamics and societal expectations associated with their cultural identities, highlighting the profound interplay between socio-cultural factors and linguistic practices. Furthermore, the study underscores the influence of cultural blending and technological advancements on language usage, showcasing how interactions among diverse cultural groups contribute to the rich linguistic diversity observed in urban settings. By offering a comprehensive analysis, this research provides valuable insights into the nuanced ways in which socio-cultural contexts shape language interactions, thus contributing to a deeper understanding of intercultural communication dynamics and offering implications for promoting social cohesion within multicultural communities. Ultimately, this study underscores the significance of recognizing and appreciating the complexities inherent in language use within diverse urban environments, paving the way for more inclusive and effective communication strategies tailored to meet the needs of multicultural societies.